SPECIFIC FEATURES OF REGULATING THE FОRECASTING SYSTEM FOR THE SOCIO-ECONОMIC DEVELОPMENT IN RUSSIA - R. Khairullina, Elmira; V. Lushchik, Irina; E. Lampsi, Oksana; V. Romanov, Igor; A. Burovkina, Lyudmila; A. Krupnov, Yuri; Yu. Butyrin, Andrey (Revista Gênero e Interdisciplinaridade, 2021)
The system of forecasting and planning the economy is being formed today in the Russian Federation. The outcome of this process is expected to be the formation of a system of priorities and goals of the socio-economic development of the country, the development and implementation of national projects and government programs. The paper gives an analysis of the theoretical and methodological aspects concerning the regulatiоn of the forecasting system of the socio-economic development in Russia. The principles of regulating the forecasting of the socio-economic development in the Russian Federation have been studied and proposals have been developed to improve the process under study. The conclusions have been drawn that forecasting is one of the important functiоns of public administration. Forecasting contributes to the identification of possible future problems of socio-economic development, substantiation and development of preventive measures of socio-economic policy, which ensures early structural, technological, institutional changes, and also gives an opportunity to adapt effectively to the specific conditions of the future situation. Forecasting also makes it possible to obtain the expected assessments of the results of the implementation of various economic policy options. Thus, forecasting allows one to pick a pоlicy option objectively that provides the desired trajectory of socio-economic development.